AI literacy in an uncertain world (Journal of Applied Learning and Teaching, 2026)
As Artificial Intelligence (AI) continues to reshape industries, education, and daily life, the ability to critically engage with AI has become essential. In an increasingly unpredictable and AI-saturated world, AI literacy has emerged as a cornerstone for effective learning, ethical reasoning, and professional adaptability. This paper conceptually examines the necessity of AI literacy in education through a theoretical and narrative approach, drawing on contemporary literature and reflective analysis. The paper urges educators and institutions to embed AI literacy across curricula through interdisciplinary design and ethical awareness. Recommendations for future research include empirical testing of AI literacy frameworks, development of reliable assessment tools, and cross-cultural analyses of AI literacy education. Ultimately, the paper underscores the enduring role of human wisdom and critical reflection in ensuring that AI serves as a catalyst for learning and professional growth rather than a replacement for human judgment.